Let's factor the expression by separating the complete square: 5a^2+13a+8=5(a^2+2a+1)+3a+3=5(a+1)^2+3(a+1)=(a+1)(5(a+1)+3)=(a+1)(5a+5+3)=(a+1)(5a+8) Also we can do it in another way by finding roots of the given polynome: 5a^2+13a+8=0 D=13^2-4*8*5=169-160=9 a1=(-13+3)/10=-1 a2=(-13-3)/10=-16/10 Now we can factor the polynome as following: 5a^2+13a+8=5(a+1)(a+16/10)=(a+1)(5a+8) - no surprises, we've obtained the same result
For our visitors we also created video where factorisation of quadratic polynom is considered. Please take a look!
College and University is a time in your life when you find your passions and your interests and you study…
APPROVED BY CLIENTS
I was very happy with the results after after a misunderstanding of the instructions of the paper. i would've liked to get some graphs or charts showing me the results from Stats, but since I didn't ask for, it's fine.